Perivascular spaces, diffusion MRI markers and cognitive decline in cerebral small vessel disease - Gemma Solé-Guardia (Cerebral Circulation - Cognition and Behavior, 2025)
Background: MRI markers, including visible perivascular spaces (PVS), diffusion tensor image analysis along the perivascular space (DTI-ALPS) index, and peak width of skeletonized mean diffusivity (PSMD) may capture the earliest pathogenesis of cerebral small vessel disease (SVD). This study aimed to elucidate the association between these markers and cognitive decline in sporadic and hereditary SVD. Methods: We included individuals from two cohorts: (1) participants with sporadic SVD from the Radboud University Nijmegen Diffusion tensor Magnetic resonance imaging Cohort (RUNDMC) and (2) participants with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) followed at the French National Referral Center. Individuals in both cohorts underwent neuroimaging and cognitive assessment over 14 years. We quantified baseline PVS burden, DTI-ALPS index and PSMD. We used linear mixed models to test their associations with longitudinal cognitive function, and Fine-and-Gray models to assess their association with incident all-cause dementia. Results: Cohort 1 included 446 individuals (mean age (SD) 65.2 years (8.9); 203 women), Cohort 2 included 164 individuals (mean age (SD) 49.9 years (12.6); 88 women). Baseline DTI-ALPS index was independently associated with better longitudinal processing speed (Cohort 1:β=0.11, 95 %CI 0.03–0.19) and cognitive index (Cohort 2:β=0.20, 95 %CI 0.06–0.33). Neither PVS burden, DTI-ALPS index nor PSMD were significantly associated with increased risk of all-cause dementia. Conclusion: These findings suggest that DTI-ALPS index may serve as a marker for cognitive decline. However, these markers have limited association with all-cause dementia risk. Future studies are needed to validate DTI-ALPS index and its link to cognitive decline.